2014
DOI: 10.1371/journal.pone.0090763
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Phenotyping of a Collection of sRNA Gene Deletion Mutants of the Haloarchaeon Haloferax volcanii

Abstract: The haloarchaeon Haloferax volcanii was shown to contain 145 intergenic and 45 antisense sRNAs. In a comprehensive approach to unravel various biological roles of haloarchaeal sRNAs in vivo, 27 sRNA genes were selected and deletion mutants were generated. The phenotypes of these mutants were compared to that of the parent strain under ten different conditions, i.e. growth on four different carbon sources, growth at three different salt concentrations, and application of four different stress conditions. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 48 publications
2
39
0
1
Order By: Relevance
“…The efficient genetic system and the possibility of massive parallel cultivation together enabled the generation of a set of 27 deletion mutants of sRNA genes and their phenotyping under 11 different growth or stress conditions. In addition, cell morphology was checked and swarming was analyzed 54 . Interestingly, 24 of the 27 sRNA gene deletion mutants exhibited a phenotype under at least one of the tested conditions, unraveling the broad importance of sRNAs in haloarchaea for many biological functions.…”
Section: In Vivo Functions Of Srnas In Archaeamentioning
confidence: 99%
“…The efficient genetic system and the possibility of massive parallel cultivation together enabled the generation of a set of 27 deletion mutants of sRNA genes and their phenotyping under 11 different growth or stress conditions. In addition, cell morphology was checked and swarming was analyzed 54 . Interestingly, 24 of the 27 sRNA gene deletion mutants exhibited a phenotype under at least one of the tested conditions, unraveling the broad importance of sRNAs in haloarchaea for many biological functions.…”
Section: In Vivo Functions Of Srnas In Archaeamentioning
confidence: 99%
“…It has recently been demonstrated that several sRNA deletion mutants of the haloarchaeon Haloferax volcanii showed a gain-offunction phenotype (82). Taken together, it may be suggested that the biological role of some sRNAs can be to stabilize the homeostasis of cells, especially when they are confronted with the multiple environmental changes that occur in real life.…”
Section: Selection Of Srnas and Construction Of Corresponding Mutantsmentioning
confidence: 99%
“…While phenotypic characterization of sRNA deletion mutants, including 10 gain-of-function phenotypes out of 27 mutants tested, confirmed their roles in metabolic regulation, stress adaptation and complex behavior [12,36], their targets are still unknown with a few exceptions. Some of these exceptions comes from the study of M. mazei cultures grown under nitrogen starvation conditions where RNA-seq experiments revealed the differential expression of a number of sRNAs in response to nitrogen availability [23,37].…”
Section: Gene Regulatory Network and Srnasmentioning
confidence: 99%
“…In H. volcanii, many intergenic sRNAs are differentially expressed in response to varying environmental conditions, including elevated temperature, osmotic stress, nutrient limitation, and 14 oxidative stress, [1,8,12,35,36]. While phenotypic characterization of sRNA deletion mutants, including 10 gain-of-function phenotypes out of 27 mutants tested, confirmed their roles in metabolic regulation, stress adaptation and complex behavior [12,36], their targets are still unknown with a few exceptions.…”
Section: Gene Regulatory Network and Srnasmentioning
confidence: 99%